Sm-Like Protein-Mediated RNA Metabolism Is Required for Heat Stress Tolerance in Arabidopsis - Okamoto, Masanori; Matsui, Akihiro; Tanaka, Maho; Morosawa, Taeko; Ishida, Junko; Iida, Kei; Mochizuki, Yoshiki; Toyoda, Tetsuro; Seki, Motoaki (Frontiers in Plant Science, 2016)
Sm-like proteins play multiple functions in RNA metabolism, which is essential for biological processes such as stress responses in eukaryotes. The Arabidopsis thaliana sad1 mutant has a mutation of sm-like protein 5 (LSM5) and shows impaired drought and salt stress tolerances. The lsm5/sad1 mutant also showed hypersensitivity to heat stress. GFP-fused LSM5/SAD1 was localized in the nucleus under optimal growth conditions. After heat stress treatment, GFP-fused LSM5/SAD1 fluorescence was also observed as small cytoplasmic dots, in addition to nuclear localization. Whole genome transcriptome analysis revealed that many genes in Arabidopsis were drastically changed in response to heat stress. More heat-responsive genes were highly expressed in lsm5/sad1 mutant at both 2 h and 6 h after heat stress treatment. Additionally, intron-retained and capped transcripts accumulated in the lsm5/sad1 mutant after heat stress treatment. In this study, we also identified non-Arabidopsis Genome Initiative (AGI) transcripts that were expressed from unannotated regions. Most of these transcripts were antisense transcripts, and many capped non-AGI transcripts accumulated in the lsm5/sad1 mutant during heat stress treatment. These results indicated that LSM5/SAD1 functions to degrade aberrant transcripts through appropriate mRNA splicing and decapping, and precise RNA metabolic machinery is required for heat stress tolerance.